The The Development of Project Assessment in Matter and Energy Subjects Using the Addie Model - Arif, Rifda Nur Hikmahwati; Nurhidayah, Nurhidayah; Fatkhulloh, Shoffan; Yanto, Nurfitra; Samputri, Salma; M, Fitrah Sukmadewi (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2025)
This study aims to develop a valid, reliable, and practical project assessment sheet instrument for the Substances and Energy course using the ADDIE model. The instrument was developed through the stages of Analysis, Design, Development, Implementation, and Evaluation. The content validity of the instrument was tested using Aiken's V formula with two expert validators and resulted in an average value of 0.913, indicating very high validity. Instrument reliability was tested using Cronbach's Alpha coefficient with a value of 0.95, indicating very high internal consistency. The practicality test of the instrument through student responses showed an average score above 4.0 on a scale of 1-5, with the percentage of positive responses of “Agree” and “Strongly Agree” reaching almost 60%, indicating that the instrument is easy to understand and use and is able to motivate students in project work. Although there is some room for improvement, this instrument is well received by students and lecturers and is suitable for use as a project-based learning evaluation tool in the Substance and Energy course.